Analysis of Stock Return Determinants in Manufacturing Companies Consistently in LQ45 Index 2018–2024 - popi dwiyanti; Ranila Suciati (School of Accountancy, University of Agung Podomoro, 2026)
This study aims to examine the effect of firm value, profitability, and systematic risk on stock returns of manufacturing firms consistently included in the LQ45 index on the Indonesia Stock Exchange during 2018–2024. This study employs a quantitative approach using panel data regression analysis. The sample consists of 14 firms selected based on purposive sampling criteria. Firm value is measured by Price to Book Value (PBV), profitability by Return on Equity (ROE), and systematic risk is measured by beta, estimated from monthly stock returns, with market returns proxied by the IHSG. The results indicate that firm value has a positive and significant effect on stock returns, suggesting that higher market valuation reflects stronger investor confidence. In contrast, profitability and systematic risk do not have a significant effect on stock returns. The insignificance of ROE indicates that investors may not rely solely on profitability indicators, while the insignificance of beta suggests that systematic risk may not be a primary consideration in this sample. Overall, the findings provide limited but specific empirical evidence regarding stock return determinants in manufacturing firms within the LQ45 index during the 2018–2024 period.